PENGARUH KEMISKINAN, PENGANGGURAN, UPAH, PERTUMBUHAN EKONOMI, DAN REALISASI BELANJA PEMERINTAH DAERAH TERHADAP INDEKS PEMBANGUNAN MANUSIA KABUPATEN PROBOLINGGO - Dita Ayu Cahyani (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2022)
All humans certainly dream of a prosperous life, but not all get a prosperous life. Therefore, the government undertakes development in order to improve the welfare of its people. Human development is important because high economic growth does not always solve social problems such as poverty, unemployment and welfare. One indicator to measure the level of welfare is the Human Development Index (HDI). This study aims to determine how much the poverty rate, the open unemployment rate, the minimum wage, economic growth, and the realization of local government spending on the Human Development Index (HDI) in Probolinggo Regency. This study uses time series data which was analyzed using multiple linear regression analysis. The results of this study indicate that simultaneously the independent variables have a significant effect on the Human Development Index. Partially, the poverty level has a significant negative effect on the Human Development Index, the minimum wage and the realization of local government spending have a significant effect on the Human Development Index. While partially, both the open unemployment rate variable and the economic growth variable have no effect on the Human Development Index in Probolinggo Regency.